Increasing Adaptive Capacity of Farmers to Climate Change thru Climate Smart Villages in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
ITC Limited and CGIAR research program on climate change, agriculture and food security (CCAFS) partnering to develop resilient agriculture production system in the ITC’s outreach areas across India. CGIAR’s Climate Smart Village (CSV) approach was integrated into the ITC’s Mission Sunehra Kal (MSK) program. This CSV-MSK integration program focus on building resilient agriculture production system through promotion of a range of climate smart agricultural technologies and practices including e-Choupal, wasteland development, soil and moisture conservation, livestock development, health and education, and gender and social inclusion program of MSK. The Mission now embraces a community of thousands of villages that are influential nuclei of change in rural localities spread over 12 States across India. By linking knowledge and technology transfer to the creation of economic and social capacity, ITC aims to bring a unique dynamic to rural development, food security and poverty alleviation. The present report highlights the work carried out under this program.